Evaluasi Pelaksanaan Program Ujian Online di SMK NEGERI 4 JAKARTA - Erni Kristiyani (Jurnal Pensil)
The Objectives of this study to determine whether the online testing program for Class XII students of Stone Concrete Construction Engineering Department at SMK 4 Jakarta has been successful or not. This research was conducted in the Department of Stone Concrete Construction Engineering SMKN 4 Jakarta in July 2013 until November 2013. The method used is the evaluative research method with the type of CIPP evaluation model (Context, Input, Process, Product), with a sample of 26 students Class XII Stone Concrete Construction Engineering Department, one of teacher Stone Concrete Construction Engineering Department, and Head of IT SMKN 4 Jakarta. The research instrument used online testing, interviews, and questionnaires. Validity test results, 10 items questionnaire is valid. While the results of the reliability test, R11 value is 0.904. To access the online testing program, Head of IT requires program of Moodle, server, internet networks, and laptop; the teachers need laptop, Hot Potatoes, and the internet networks; while the students need laptop and internet networks. The curriculum used is the Kurikulum Tingkat Satuan Pendidikan (KTSP). The average score that student obtained from online testing is 72, and this score is lower than a Kriteria Ketuntasan Minimal (KKM) which has been determined 75. From the calculation of the questionnaire, percentage of successful online testing program is only 56.69% of the respondents expected. During the implementation of the online testing program, there are some issues such as school wifi network can not be used, the server often down, students must bring their own laptops and modems, and as well as a hot classroom. The impact of online testing program that is obtained by the school teachers and students can operate computers and the Internet as a means of learning evaluation. Thus, the overall implementation of the online testing program at SMK 4 Jakarta can be said to have not succeeded and need for improvement, especially in school’s internet networks and facilities to support the online testing program